Nostoc an alternative as a nutritional supplement to combat anemia: RSL - Canchari Suarez , Mari Luz (2024)
The purpose of this systematic review was to investigate the potential of Nostoc seaweed, also known as Cushuro, as a nutritional supplement in various food products, and its possible benefits in combating public health problems, generally anemia and malnutrition. The methodology used included an exhaustive review of theoretical and empirical sources, with questions formulated following the PICOC format and the PRISMA method. Specific keywords were established and search equations were developed in the Scopus database. In addition, criteria were applied to select articles that met the necessary requirements. Initially, 4932 relevant studies were found, and after applying rigorous methodological criteria, 86 articles were selected that turned out to be relevant to this research. The analysis of these 30 articles allowed significant results to be obtained, highlighting that 19 of them highlight the potential of Nostoc as a nutritional supplement in various food products, including basic foods in the family basket. Likewise, the warning about its benefits to combat problems of anemia and malnutrition is highlighted. The discussion focuses on the possible results obtained from the questions posed in the systematic review, using the information collected from the selected articles. The role of Nostoc in a variety of products is highlighted, in addition to its contribution to local gastronomy by enriching traditional dishes and diversifying the diet. This systematic literature review confirmed the potential of Nostoc seaweed as a nutritional supplement in different products, presenting a promising alternative to combat public health problems such as anemia and malnutrition, especially in the child population.